(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
The general use of AI technology, especially in public sectors like security and even in the medical field, has been subject to a number of questions to do with ethics. This paper aims to understand the ethical dilemmas concerning the instantiation of Artificial Intelligence in these fields, specifically privacy, bias, responsibility, and openness concerns. In security, advanced technologies like facial recognition and predictive policing attract concerns pertaining to violation of privacy, importation of race bias, and lack of social control, among others. In health care, the AI systems employed in the diagnosis and treatment of patients call into question issues to do with patient choices, data privacy, and discrimination in medical treatment. Within the scope of the paper, the author considers contemporary ethical standards and legislation regulating AI creation and finds some deficiencies. In response to these issues, some of the potential work for the future highlighted in the paper includes enhancing the legal policies in the area of AI, insisting on the importance of ethical multi-disciplinary research, and creating awareness of the effects of AI in society. It underlines the requirement for responsible and explainable AI, the availability of efficient tools helping in monitoring and controlling AI, and increased people’s involvement in creating AI policies to state that the launched AI technologies will be compliant with the people’s benefit. With these suggestions, the paper sought to add knowledge to the ongoing discussion on AI ethics and ensure that decent utilization of AI systems is enhanced with reverence to human rights and ethical norms.